2006
DOI: 10.1192/bjp.bp.105.014571
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options in moderate and severe depression: decision analysis supporting a clinical guideline

Abstract: Combination therapy is likely to be a cost-effective first-line secondary care treatment for severe depression. Its cost-effectiveness for moderate depression is more uncertain from current evidence. Targeted combination therapy could improve resource utilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 26 publications
0
44
0
1
Order By: Relevance
“…Costs were assessed from a third-party payer perspective mainly. All studies considered intervention costs, while 5 studies reported outpatient costs additionally [20,21,22,24,25]. Four studies included inpatient costs and medication [21,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costs were assessed from a third-party payer perspective mainly. All studies considered intervention costs, while 5 studies reported outpatient costs additionally [20,21,22,24,25]. Four studies included inpatient costs and medication [21,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were modelling studies taking the whole population of a country into account [20,21,22,23]. The remaining 2 studies were randomized controlled trials (RCTs) focussing on specific adult populations, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it may stimulate and inform future research into the causes and predictors of illness progression from one stage to the next. Secondly, by adding an early description of the individual's risk of progression to a specific illness stage, it may help the clinician to estimate the value of performing a specific investigation or to make utility-based judgments on treatment selection, thus personalizing the assessment and treatment process and optimizing overall efficiency of care (Hatcher, 1995;Owens et al, 1997;Simon et al, 2006;Sox et al, 2013;Werneke et al, 2012;Yokota and Thompson, 2004). Treatment choices informed by such risk may, for example, involve early clozapine initiation (Kaneda et al, 2010;Remington et al, 2013), targeted early provision of cognitive remediation training or cognitive enhancing treatments (Koike et al, 2013;Medalia and Saperstein, 2013;Wood et al, 2013), early specialized vocational rehabilitation (Killackey et al, 2008), specific neuroprotective strategies (Swerdlow, 2011), or targeted augmentation with anti-inflammatory medications (Sommer et al, 2014) or metabolic modifiers such as metformin (Correll et al, 2013;Guest et al, 2013aGuest et al, 2013b.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Sólo la satisfacción con el tratamiento fue significativamente mayor en el grupo de intervención con atención especializada 56 . Otra publicación basada en la revisión sistemática de la literatura analiza siete estudios que comparan la terapia cognitivo conductual más antidepresivos con sólo terapia con antidepresivos en 831 pacientes con depresión moderada o severa atendidos en el nivel secundario, revela que la probabilidad de lograr remisión y presentar menor riesgo de recaída es mayor con la terapia combinada comparada con sólo medicación antidepresiva, a los 12 meses de seguimiento; donde la terapia combinada incrementa en 0,16 la probabilidad de tratamiento exitoso por paciente, en un período de 15 meses, pero con un mayor costo 57 . En Chile, en el área del tratamiento de la depresión en atención primaria, se ha realizado un estudio controlado con distribución aleatoria para un tratamiento multicomponente escalonado para la depresión en mujeres 58 , investigación en depresión post parto 30 , un estudio de costo-efectividad en mujeres 29 y un ensayo clínico controlado aleatorizado de farmacoterapia con monitorización telefónica para mejorar el tratamiento de la depresión 31 .…”
Section: Investigación En Relación Con El Curso Y Tratamiento De La Dunclassified